2011
DOI: 10.1371/journal.pone.0029558
|View full text |Cite|
|
Sign up to set email alerts
|

Oxygen: A Fundamental Property Regulating Pelagic Ecosystem Structure in the Coastal Southeastern Tropical Pacific

Abstract: BackgroundIn the southeastern tropical Pacific anchovy (Engraulis ringens) and sardine (Sardinops sagax) abundance have recently fluctuated on multidecadal scales and food and temperature have been proposed as the key parameters explaining these changes. However, ecological and paleoecological studies, and the fact that anchovies and sardines are favored differently in other regions, raise questions about the role of temperature. Here we investigate the role of oxygen in structuring fish populations in the Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 44 publications
9
167
2
1
Order By: Relevance
“…2 B and D). Although other mechanisms of anchovy-sardine dynamics have been proposed related to coastal vs. wind-stress curl upwelling (24) and oxygen content of waters (27), results here suggest that prey preferences and variation in the feedback loop between bottom-up and topdown forcing due to fronts lead to similar patterns. It is likely that a combination of these mechanisms works in concert to drive observed fluctuations between anchovies and sardines.…”
Section: Significancecontrasting
confidence: 50%
See 1 more Smart Citation
“…2 B and D). Although other mechanisms of anchovy-sardine dynamics have been proposed related to coastal vs. wind-stress curl upwelling (24) and oxygen content of waters (27), results here suggest that prey preferences and variation in the feedback loop between bottom-up and topdown forcing due to fronts lead to similar patterns. It is likely that a combination of these mechanisms works in concert to drive observed fluctuations between anchovies and sardines.…”
Section: Significancecontrasting
confidence: 50%
“…The change in zooplankton size spectra due to front dynamics offers an alternate mechanism for regime shifts from anchovy-to sardine-dominated systems beyond those related to physical, biochemical, and climate drivers (24)(25)(26)(27). Weak fronts lead to higher levels of smaller phytoplankton and zooplankton (e.g., dinoflagellates and microzooplankton, Fig.…”
Section: Significancementioning
confidence: 99%
“…Increased CO 2 and decreased O 2 move the aragonite compensation depth (Feely et al 2008) and oxycline (Bertrand et al 2011) upward, compressing the habitat for both competitors and predators of anchovy and sardine (Netburn & Koslow 2015).…”
Section: Distribution Shiftsmentioning
confidence: 99%
“…Bertrand et al (2011;this symposium) for example demonstrated the influence of oxygen concentrations on the distribution and abundance of various pelagic species on the Peruvian coast. At an individual level, the dynamic energy budget (DEB, Kooijman 2000) model has helped to discriminate between the reproductive strategies of sardine and anchovy (Gatti et al, this symposium).…”
Section: Population/species Scale: Still Advancingmentioning
confidence: 99%